2019
DOI: 10.3389/fbioe.2019.00271
|View full text |Cite
|
Sign up to set email alerts
|

MoCloFlex: A Modular Yet Flexible Cloning System

Abstract: Modern cloning solutions are gradually replacing classical cloning methods. Current systems make use of libraries with predefined DNA parts that are joined by Golden-Gate reactions. However, these systems still suffer from specific inflexibilities and the lack of inter-compatibility. Here, we present Flexible Modular Cloning (MoCloFlex) which overcomes this inflexibility by introducing a set of linker- and position-vectors allowing free unit arrangement. Our system, therefore, provides a convenient way to desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…This fact might require elimination of incompatible restriction sites if parts from different toolboxes are to be used in higher level plasmids. In addition to the standard Phytobrick fusion sites, we designed novel fusion sites for Marburg Collection-specific part categories, namely ORI, AR and 5’ and 3’ connector parts, as described previously (27). To facilitate standard cloning workflows, we defined eight level 0 part categories required for the construction of a level 1 plasmid (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…This fact might require elimination of incompatible restriction sites if parts from different toolboxes are to be used in higher level plasmids. In addition to the standard Phytobrick fusion sites, we designed novel fusion sites for Marburg Collection-specific part categories, namely ORI, AR and 5’ and 3’ connector parts, as described previously (27). To facilitate standard cloning workflows, we defined eight level 0 part categories required for the construction of a level 1 plasmid (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…MoCloFlex, a new modular cloning system for flexible de novo part/plasmid assembly, has been developed, and it has been revealed that it can be used to plan, build, and isolate a custom plasmid within 24 h. This leads to reduced costs and time consumption (Klein et al, 2019). In one study, it was reported that the E. coli "TatExpress" strain resulted in the delivery of 5.4 g/l of human growth hormone to the periplasm by the Tat pathway using fed-batch fermentation.…”
Section: Escherichia Colimentioning
confidence: 99%
“…2A). Additionally, the INS entry vector is level 1 MoClo 19 , MoCloFlex 20 and Marburg Collection 22 compatible. Hence, level 1 transcription units build with the MoClo-System or Marburg Collection as well as larger assemblies build with MoCloFlex can be cloned into the INS entry vector.…”
Section: Modular Assembly Of the Pswap Plasmidmentioning
confidence: 99%
“…A standard assembly of pSwap comprises 7 parts. With a growing number of parts in a golden gate reaction, the number of correctly assembled plasmids decrease 20 . The selection for a correctly assembled pSwap is guided by co-expression of the deoxyviolacein pathway, whose individual genes are distributed among the parts T1, T2, H1α and HA.…”
Section: Modular Assembly Of the Pswap Plasmidmentioning
confidence: 99%
See 1 more Smart Citation